The Improvement of Rice Postharvest Technology in Sub-Optimal Land - Hasbi Hasbi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Hasbi. 2012. The Improvement of Rice Postharvest Technology in Sub-Optimal Land. PLSO 1(2):186-196. Rice is the most exerted food crop commodity in Indonesia. Rice production has continuously been increased in order to support food security policy. Improvement of cultivation technology has been proved to increase rice production significantly. Increase in rice production should be followed by the improvement of rice quality based on the standard and consumer preference. The improvement in quality may also be enhanced by proper postharvest technology. Improvement of rice quality will result in more added value on rice. Therefore, proper technology which includes production, harvest, and post harvest should be done in an integrated manner in order to increase rice quality and at the same time decrease weight loss. Rice postharvest technology consists of harvesting, threshing, transportation, drying, cleaning and storage. These postharvest activities are often followed by rice milling. However, farmers awareness and knowledge regarding proper postharvest technology are lacking and its application is considered low. Improvement of postharvest handling technology should be prioritized to include three stages, which are harvesting, threshing and drying due to high loss occured in these stages. The improvement of harvest and postharvest technologies should incorporate human resource ability and information dissemination based on the principles of Good Handling Practices (GHP).